2018
DOI: 10.1016/j.jtho.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased Response Rates to Salvage Chemotherapy Administered after PD-1/PD-L1 Inhibitors in Patients with Non–Small Cell Lung Cancer

Abstract: The ORR for SCAI was significantly higher than that for LCBI. These data indicate that anti-PD-1/PD-L1 inhibitors could make tumors more vulnerable to subsequent chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
181
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(208 citation statements)
references
References 15 publications
19
181
3
5
Order By: Relevance
“…Our data indicate that the combination of docetaxel plus ramucirumab as a VEGFR2 inhibitor may contribute to the improved response rate. 4,5 Previous studies suggest that immunotherapy may introduce tumor synergistic effects to subsequent cytotoxic therapy; our results are consistent with this finding . Moreover, it has been reported that therapeutic level of anti‐PD‐1 is maintained when chemotherapy is administered because of the long half‐life of the PD‐1 antibody .…”
Section: Discussionsupporting
confidence: 90%
“…Our data indicate that the combination of docetaxel plus ramucirumab as a VEGFR2 inhibitor may contribute to the improved response rate. 4,5 Previous studies suggest that immunotherapy may introduce tumor synergistic effects to subsequent cytotoxic therapy; our results are consistent with this finding . Moreover, it has been reported that therapeutic level of anti‐PD‐1 is maintained when chemotherapy is administered because of the long half‐life of the PD‐1 antibody .…”
Section: Discussionsupporting
confidence: 90%
“…The sequence of chemotherapy following nivolumab improved anti‐tumor activity regardless of tumor PD‐L1 expression, but the reverse sequence did not. Similar to these findings, four retrospective studies of salvage chemotherapy, including a case–control study, showed a high ORR of 38% and median PFS of approximately four months in previously treated patients with NSCLC . In the case–control study, the odds ratio for achieving an objective response to salvage chemotherapy was more than three times higher .…”
Section: Discussionsupporting
confidence: 62%
“…We have reported the drastic regression of lung cancer cases treated with chemotherapy following nivolumab, which is known as salvage chemotherapy . Several recent studies have also shown that the combination therapy of PD‐1 inhibitors with anti‐cancer drugs, including salvage chemotherapy, produces high anti‐tumor activity in some patients . Salvage chemotherapy showed a high objective response rate of 38% (95% confidence interval [CI] 31.3–44.7%) in a total of 200 cases obtained from four retrospective studies …”
Section: Introductionmentioning
confidence: 99%
“…This was a retrospective cohort study of patients with advanced‐stage NSCLC who received palliative pembrolizumab. We retrospectively identified 172 patients who received pembrolizumab between July 2014 and January 2018 from the lung cancer immunotherapy registry of Samsung Medical Center, and who had undergone spirometry testing within the past 3 years. Patients with small cell lung cancer ( n = 3), and those who received ICI treatment for an adjuvant purpose ( n = 14), received ICI treatment previously ( n = 7), underwent combined treatment with other types of ICIs ( n = 2), or died within 2 weeks of ICI treatment initiation ( n = 13) were excluded.…”
Section: Methodsmentioning
confidence: 99%